Move on Malaysian art - Abdullah, Sarena (Balai Seni Visual Negara (BSVN), 2014)
Art in Malaysia today has grown into many different media and approaches. Fine art has meant art forms created mainly for aesthetics, differentiating them from applied arts created to serve some practical function. Traditionally. the fine arts are drawing, painting, sculpture. photography and printmaking. However, since the 1990's, artw01ks that cross these traditional boundaries hove been produced extensively-names such as liew Kungyu, Wong Hoy Cheong, fan Chin Kvan. Hasnul Jamal Soidon. Nlanjon Rajah. are among those who hove explored the artistic fi~d beyond the pointing trocfition.